2019
DOI: 10.3389/fendo.2019.00877
|View full text |Cite
|
Sign up to set email alerts
|

Di (2-ethylhexyl) Phthalate Exposure Impairs the microRNAs Expression Profile During Primordial Follicle Assembly

Abstract: This research was performed to estimate the potential effects of Di (2-ethylhexyl) phthalate (DEHP) on changes of ovarian miRNA expression profile during mouse primordial follicle assembly using miRNAs-seq analysis. The ovaries of newborn mice were collected and in vitro cultured with different concentration of DEHP for 72 h. Then they were prepared for miRNAs-seq analysis. The results indicated that DEHP exposure altered ovarian miRNA expression profile of newborn mice. Eighteen differentially expressed miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In women, urinary concentrations of phthalate metabolites are associated with the expression of extracellular vesicle miRs in follicular fluid (Martinez et al 2019). The exposure to DEHP altered the ovarian miR expression profile of newborn mice (Zhang et al 2019). In a previous work, we found that female mice chronically exposed to a mixture of phthalates and alkylphenols show a decrease in the expression of ovarian steroidogenesis genes, including CYP19A1, along with a significant decrease in E 2 plasmatic levels (Patino-Garcia et al 2018).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In women, urinary concentrations of phthalate metabolites are associated with the expression of extracellular vesicle miRs in follicular fluid (Martinez et al 2019). The exposure to DEHP altered the ovarian miR expression profile of newborn mice (Zhang et al 2019). In a previous work, we found that female mice chronically exposed to a mixture of phthalates and alkylphenols show a decrease in the expression of ovarian steroidogenesis genes, including CYP19A1, along with a significant decrease in E 2 plasmatic levels (Patino-Garcia et al 2018).…”
Section: Introductionmentioning
confidence: 75%
“…New research has proposed a link between these changes in mRNA expression and the loss of the post-transcriptional regulation by miRs or other sncRNAs (Sandhu et al 2012) affecting female fertility (Ahmed et al 2017, Lite et al 2019. Studying the miRome (miR expression) profile, Zhang et al showed that only some miRs were deregulated and the progesterone-mediated oocyte maturation signaling pathway was one of the most altered in newborn mice ovaries after exposure to DBP (Zhang et al 2019). Interestingly, mmu-miR-200a-5p was reported to be upregulated.…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…to the reduced Bax/Bcl2 ratio, which may initiate testicular apoptosis in Wistar rats (Helmy et al, 2020). In terms of female reproductive toxicities, ovarian development and primordial follicular assembly can be stressed by DEHP-induced miRNA expression, for instance, miR-19a-3p (Zhang et al, 2019). Similar effects were also recorded under the mice study by Liu et al (2018) By crossing blood-brain barrier and entering into the nervous system, DEHP can also affect neuronal growth (Smith, MacDonald, & Holahan, 2011;Tanida et al, 2009;Testa et al, 2012).…”
Section: Di-ethylhexyl Phthalatementioning
confidence: 72%
“…DEHP‐induced aberrant expression of oxidative stress responsive miRNAs (miR‐126 and miR‐181a) has also been implicated to the reduced Bax / Bcl2 ratio, which may initiate testicular apoptosis in Wistar rats (Helmy et al, 2020). In terms of female reproductive toxicities, ovarian development and primordial follicular assembly can be stressed by DEHP‐induced miRNA expression, for instance, miR‐19a‐3p (Zhang et al, 2019). Similar effects were also recorded under the mice study by Liu et al (2018) that DEHP down‐regulated the expression of follicle development‐related factors, c‐Kit , Kitl , Gdf9 , and Atm with the upregulation of ovarian miRNAs (let‐7b, miR‐17‐5p, miR‐181a, and miR‐151), which suppress follicular granulosa cell proliferation.…”
Section: Epigenetic Changes Link Ecs To Adverse Health Outcomesmentioning
confidence: 99%
“…It is best known as an endocrine disruptor that disrupts the regulation and action of thyroid hormones [3]. In addition, DEHP and its metabolites have the potential to induce testicular, ovarian, renal, neuro, and cardiovascular toxicity [4][5][6]. Both occupational and environmental routes of exposure to DEHP are of concern for human health [7].…”
Section: Introductionmentioning
confidence: 99%